2013
DOI: 10.1371/journal.pone.0055397
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Seroadaptive Practices from before to after Diagnosis of Recent HIV Infection among Men Who Have Sex with Men

Abstract: ObjectiveWe assessed changes in sexual behavior among men who have sex with men (MSM), before and for several years after HIV diagnosis, accounting for adoption of a variety of seroadaptive practices.MethodsWe collected self-reported sexual behavior data every 3 months from HIV-positive MSM at various stages of HIV infection. To establish population level trends in sexual behavior, we used negative binomial regression to model the relationship between time since diagnosis and several sexual behavior variables:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…HIV diagnosis generally compels individuals to alter sexual behaviour to reduce risk for onward transmission,53 and seroadaptive UAI behaviours may constitute a majority of risk-reduction practices following seroconversion among MSM; longitudinal studies and behavioural intervention trials indicate HIV-positive MSM have greater success maintaining serosorting and strategic positioning practices than consistent condom use as risk-reducing strategies 20 22 54. The internet may appeal to HIV-positive MSM wishing to initiate UAI encounters by providing an anonymous interface for disclosing HIV-positive serostatus 12 13.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HIV diagnosis generally compels individuals to alter sexual behaviour to reduce risk for onward transmission,53 and seroadaptive UAI behaviours may constitute a majority of risk-reduction practices following seroconversion among MSM; longitudinal studies and behavioural intervention trials indicate HIV-positive MSM have greater success maintaining serosorting and strategic positioning practices than consistent condom use as risk-reducing strategies 20 22 54. The internet may appeal to HIV-positive MSM wishing to initiate UAI encounters by providing an anonymous interface for disclosing HIV-positive serostatus 12 13.…”
Section: Discussionmentioning
confidence: 99%
“…We identified observational studies comparing UAI prevalence within MSM's online-initiated and offline-initiated sexual encounters with male partners. We limited our search to studies conducted in the USA, Canada, Great Britain, and Australia and New Zealand; most studies were undertaken in these countries, and these countries have generalisable seroadaptive behaviour and HIV resurgence patterns among MSM 4 5 20. We excluded studies not disaggregating encounters according to initial online/offline contact; prospective/pilot studies; and studies using snowball or respondent-driven sampling if quantitative analyses were not undertaken to assess whether these methods yielded representative samples.…”
Section: Search and Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, men who discover that they are HIV positive may adapt their behavior to avoid onward transmission of HIV. 31 Although testing might reduce disparities to an extent, half of the perceived-negative or unknown-status partners of black MSM knew their HIV status, which suggests that changes must be made to current HIV serodiscussion practices among black MSM and their partners, by starting the discussion, promoting accurate serodisclosure among HIV-positive men, or improving clarity when discussing HIV status. Bird and colleagues 21 found that HIVpositive black men were less likely than white men to disclose HIV status to HIV-negative, HIV-unknown, and other HIVpositive partners, but that HIV-positive black men who did disclose were less likely to engage in UAI with HIV-negative and unknown-status men.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have documented that persons entering correctional facilities report high rates of HIV sex risk behaviors (e.g., mean number of partners 36.1; unprotected sex at last sex 70 %; 66 % with at-risk partner) before incarceration [13,32,33]. Prior research has documented that learning of one's HIV infection is associated with reductions in HIV risk behavior [34][35][36]. The majority of our study participants had become aware of their HIV infection before this incarceration and may have already reduced their sex risk behaviors.…”
Section: Discussionmentioning
confidence: 99%